Health and environmental applications of biosensing technologies : clinical and allied health science perspective - Veerapandian, Murugan; Joseph, James; Marimuthu, Mohana (Elsevier, 2024)
With emerging biological threats from pathogenic microorganisms and increasing environmental pollutants, it is essential to ensure the safety needs of individuals and the ecosystem are met. Modern materials science and engineering has evolved over the years to better develop devices to test abnormalities. Affordability, accessibility, and reliability of any analytical system is the prime necessity for a modern diagnostic application. Health and Environmental Applications of Biosensing Technologies: Clinical and Allied Health Science Perspective presents a detailed overview on biosensor design systems and optimal fabrication technologies to create a greater impact on various industries and help organizations break existing performance tradeoffs to deploy biosensor technologies across inter/transdisciplinary businesses. The book presents novel and emerging trends in biosensor design and healthcare applications focused on API detection, communicable/non-communicable disease diagnosis, food quality monitoring, agro-environmental analysis, bio-defense, and industrial pollutant sensing. In addition, wearable biosensors, commercial products, and safety regulations for biosensing technologies are summarized.